De repente, não mais que de repente, gramaticalizando... - Coutinho, Nastassia Santos Neves (2016)
Focusing on Usage based models of language, the present study aims to analyze quantitatively and qualitatively the expression “de repente”, in Portuguese speech, in order to investigate if the polysemy of this use could be explained by grammaticalization. Some works, such as the ones done by Siqueira (2014) and by Pontes and Peterson (2009), have already shown that the expression “de repente” admits different semantic functions, including: adverb of time and epistemic modality. Our hypothesis is that these uses can be arranged on a scale of abstraction, they are gradual and unidirectional, from the most concrete to more abstract or less subjective to more subjective, what could be an indication that this expression is on trajectory of grammaticalization. To verify that hypothesis, we analyze the sample of two oral corpora: PortVix - Portuguese spoken in the city of Vitória (YACOVENCO, 2009; YACOVENCO et al, 2012.) and Sample Censo 2000 (PAIVA; DUARTE, 2003) of PEUL (Study Program on the Use of Language) – Rio de Janeiro. By using the Sociolinguistic method, the data is quantified to identify the most recurrent properties of each one of the meanings of the expression “de repente”. Our study in apparent time presented the epistemic value as the most productive one, and one aspect that stands out in the analysis is that this value occurs mainly in contexts where "de repente" is used as a reinforcing element of the value of possibility, competing with other modalizing elements. The influence of context on the function performed by the expression is characterized as a metonymy process, by means of subjectivity (TRAUGOTT, 2010), resource used to present distancing from the speaker in relation to the state of things described.